La cohesión gramatical del español de los migrantes ancashinos bilingües de la asociación Carolina del distrito de Carabayllo - Silvestre Herrrera, César (2020)
This article describes the use of the grammatical cohesion mechanism of ancashinos migrants who constitute a population of students and residents of the Carolina Association of the Carabayllo District. The study is based on the linguistictheory of the text of Van Dijk, morphosyntactic theory and sociolinguistic inorder to analyse the cohesion employed by the bilingual Spanish Quechua. Likewise, a comparison is made with the corresponding grammatical cohesion ofthe standard dialect.